Terminological subset of the International Classification for Nursing Practice for patients hospitalized due to burns - Ilisdayne Thallita Soares da Silva; Harlon França de Menezes; Vinicius Lino de Souza Neto; José Renato Paulino de Sales; Paulino Artur Ferreira Sousa; Richardson Augusto Rosendo da Silva (SciELO, 2021)
ABSTRACT Objective: To develop a proposal of a terminological subset of the International Classification for Nursing Practice for burned patients. Method: This is a methodological study following the steps: identification of clinical findings; mapping of terms; construction of statements of diagnoses/results and nursing interventions; content validation of statements; and structuring of the subset with the theoretical model of Basic Human Needs. Content validation was performed by 26 specialist nurses, through the Content Validity Index, with statements ≥ 0.80 being considered validated. Results: A total of 36 diagnoses/results and 119 interventions were validated. Among these, the ones with the highest index were: Respiratory System Function, Impaired/Respiratory System Function, Effective; Volume of Fluids, Impaired/Volume of Fluids, Effective; Burn Wound/Wound Healing, Effective; Pain, Acute/Pain, Absent, and as interventions: To Monitor Vital Signs; to Monitor Fluid Balance; to Treat Skin Condition; to Assess Response to Pain Management (Control). Conclusion: The validated statements depict the burned people basic human needs, with the psychobiological ones being the most prevalent.